XABAR KOMMUNIKACIYA TEXNOLOGIYALARÍNÍŃ FIZIKA PANIN OQÍTÍWDAǴÍ ÁHMIYETI - Kadirimbetova, G.R. (SCIENCE and SOCIETY, 2021)
The article discusses the tasks of improving the quality of the education system, the role of computer technologies in solving these problems. Today, improving the technological base of the educational process through the introduction of modern technical means is the basis for the modernization of the education system. Because a computer is a source of new information for students and a tool for intellectual activity.